Characterization of H7N9 influenza A viruses isolated from humans - Watanabe, Tokiko; Kiso, Maki; Fukuyama, Satoshi; Nakajima, Noriko; Imai, Masaki; Yamada, Shinya; Murakami, Shin; Yamayoshi, Seiya; Iwatsuki-Horimoto, Kiyoko; Sakoda, Yoshihiro; Takashita, Emi; McBride, Ryan; et al. (Nature (London), 2013)
Here, biological attributes of two early human isolates of the newly emerged H7N9 influenza viruses are characterized: the potential of these viruses to infect and/or transmit within various animal models is discussed, as is their relative sensitivity to neuraminidase inhibitors and experimental polymerase inhibitors compared to an H1N1 pandemic strain. Transmission of emerging H7N9 virus By 20 July 2013, there had been 134 laboratory-confirmed human cases of infection with avian influenza A H7N9 virus infection, including 43 deaths. Yoshihiro Kawaoka and colleagues characterize the biology of two recent isolates of the virus. They provide a wealth of data from infections in mice, pigs, macaques and ferrets. H7N9 virus is shown to be less sensitive to neuraminidase inhibitors than pandemic H1N1 virus, but equally susceptible to an experimental polymerase inhibitor. Terrence Tumpey and colleagues determine the capacity of two clinical H7N9 isolates to cause disease and transmit between mammals. They show that the virus can replicate in human airway cells and in the respiratory tract of ferrets to a higher level than can seasonal H3N2 virus, and show higher lethality in mice than genetically related H7N9 and H9N2 viruses. In transmission studies, the H7N9 virus showed limited transmission in ferrets by respiratory droplets. Ron Fouchier and colleagues investigate the transmissibility of H7N9 virus between ferrets. They show that airborne transmission can occur, but inefficiently. They also show that on passage in ferrets, virus variants that have higher avian receptor binding, higher pH of fusion and lower thermostability are selected, and they suggest that these characteristics may result in reduced transmissibility. Avian influenza A viruses rarely infect humans; however, when human infection and subsequent human-to-human transmission occurs, worldwide outbreaks (pandemics) can result. The recent sporadic infections of humans in China with a previously unrecognized avian influenza A virus of the H7N9 subtype (A(H7N9)) have caused concern owing to the appreciable case fatality rate associated with these infections (more than 25%), potential instances of human-to-human transmission 1 , and the lack of pre-existing immunity among humans to viruses of this subtype. Here we characterize two early human A(H7N9) isolates, A/Anhui/1/2013 (H7N9) and A/Shanghai/1/2013 (H7N9); hereafter referred to as Anhui/1 and Shanghai/1, respectively. In mice, Anhui/1 and Shanghai/1 were more pathogenic than a control avian H7N9 virus (A/duck/Gunma/466/2011 (H7N9); Dk/GM466) and a representative pandemic 2009 H1N1 virus (A/California/4/2009 (H1N1pdm09); CA04). Anhui/1, Shanghai/1 and Dk/GM466 replicated well in the nasal turbinates of ferrets. In nonhuman primates, Anhui/1 and Dk/GM466 replicated efficiently in the upper and lower respiratory tracts, whereas the replicative ability of conventional human influenza viruses is typically restricted to the upper respiratory tract of infected primates. By contrast, Anhui/1 did not replicate well in miniature pigs after intranasal inoculation. Critically, Anhui/1 transmitted through respiratory droplets in one of three pairs of ferrets. Glycan arrays showed that Anhui/1, Shanghai/1 and A/Hangzhou/1/2013 (H7N9) (a third human A(H7N9) virus tested in this assay) bind to human virus-type receptors, a property that may be critical for virus transmissibility in ferrets. Anhui/1 was found to be less sensitive in mice to neuraminidase inhibitors than a pandemic H1N1 2009 virus, although both viruses were equally susceptible to an experimental antiviral polymerase inhibitor. The robust replicative ability in mice, ferrets and nonhuman primates and the limited transmissibility in ferrets of Anhui/1 suggest that A(H7N9) viruses have pandemic potential.